From mine to user : production and procurement systems of Siliceous rocks in the European Neolithic and Bronze Age : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France) /: production and procurement systems of Siliceous rocks in the European Neolithic and Bronze Age : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France). (2021) - Unknown
No abstract available